An analysis of Iranian negotiating style as evidenced from the 1979 US hostage crisis and the Iran-EU nuclear negotiations from 2003 to 2006 - Solomon, Hussein (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2010.